Impacts of maize cropping systems on soil microbiome phytochemistry and trophic interactions between the fall armyworm, Spodoptera frugiperda (J. E. Smith) and its endoparasitoid Cotesia icipe (Fernandez-Triana & Fiaboe) - Yusuf, Abdullahi Ahmed (University of Pretoria, 2025)
Thesis (PhD (Entomology))--University of Pretoria, 2025.